The effect of irrigation Treatments and salicylic acid in some vegetative traits and physiological of wheat crop: Ali N. Farhood* Raisan A.AL- Zobiday** Salam A. Khate*** Firas D.Abed**** Ayad W. Abbas - ناظم فرهود, علي; احمد الزبيدي, ريسان; علي كحيط, سلام; ذياب عبد, فراس; وعد العناوي, اياد (Journal of Kerbala for Agricultural Sciences, 2017)
A field experiment was conducted during the winter season ( 2014 -2015) at one of the farmers field in Annana region / Hilla / Babil (Latitude N and Longitude East) , The experiment was arranged as a split-split plot in a Randomized Complete Block Design with three replication.Treatments of irrigation (Full irrigation (Ir.F) , depriving irrigation one in the tillers stage (Ir.D1), depriving irrigation in the elongation stage (Ir.D2) and depriving irrigation in each of the tillers stage+elongation stage (Ir.D3) occupied the main plots. While, treatments of application salicylic such as (0.5 ,1 and 1.5 mM.L-1 water) and its code as (SA1.S, SA2.S and SA3.S) sequentially as well as a the treatment comparison (DW.S), occupied in the sub plots. The results showed that the treatment of depriving irrigation one in the tillers stage + elongation stage (Ir.D3) caused a higher reduction in the traits plant height (cm), the number of tillers (tiller.m-2), flag leaf area (cm2), spike length (cm), the relative water content (%),chlorophyll content ( spad ) , number of grains per spike (grain.spike-1) and grain yield (tons. ha-1) At a rate of 23.81%, 20.38%, 29.78%, 27.40 %, 21.56%, 22.96%, 35.97% and 50.69% sequentially for the treatment comparison (Ir.F). Treatment caused sprayed salicylic acid a concentration of 1.5 mM.L-1 (SA3.S) a significant increase in the highest qualities of the studied plant height (cm), the number of tillers (tiller.m-2), flag leaf area (cm2) and spike length (cm), the relative water content(%), chlorophyll content (spad), number of grains per spike (grain.spike-1) and grain yield (tons. ha-1) rates stood at 7.70%, 6.71%, 13.40%, 5.40% , 9.0%, 8.27%, 9.44% and 17.36% sequentially for the treatment comparison sprayed with water only (DW.S).